Acceptability and feasibility of a parent‐targeted dietary intervention in young survivors of childhood cancer: "Reboot". Issue 9 (10th July 2020) - Touyz, Lauren M.; Cohen, Jennifer; Garnett, Sarah P.; Grech, Allison M.; Gohil, Paayal; Cohn, Richard J.; Wakefield, Claire E.
Abstract: Background: Assess the acceptability and feasibility of delivering Reboot, a telephone dietary intervention to parents of pediatric cancer survivors. The research question asks whether tailored dietary support is acceptable and feasible to deliver to parents of young cancer survivors who have recently completed cancer treatment? Procedure: Pre‐post study. Nineteen parents of pediatric cancer survivors (aged 2‐13 years) in remission, who had received cancer treatment at a tertiary children's hospital, less than 5 years prior to the intervention. Participants received four weekly 45‐min telephone sessions led by a psychologist or dietitian and one postintervention booster session 6 weeks later. Sessions addressed strategies to increase children's vegetable and fruit intake. Results: Of the 19 parents who started the intervention, 14 completed all sessions within 8 weeks and 12 completed the booster session within 10 weeks. The mean session duration was 47 min. All participants reported that Reboot increased their confidence and knowledge about promoting healthy eating habits to their child. Conclusions: Reboot is an acceptable intervention in young cancer survivors aimed at increasing vegetable and fruit intake after cancer treatment. Implications for cancer survivors: The results from the Reboot pilot provides preliminary evidence that a targeted intervention to improve the diets of childhood cancer survivors may be feasible with future modification.